Local limit theorems and asymptotic expansions for non-stationary Markov chains - Statulevičius, V. (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: B. Статулявичюс. Локальные предельные теоремы и асимптотические разложения для неоднородных цепей Маркова V. Statulevičius. Lokalinės ribinės teoremos ir asimptotiniai išdėstymai nehomogeninėms Markovo grandinėms